Environmental sustainability of advanced biofuels. (2nd September 2013) - Davis, Sarah C.; Kucharik, Christopher J.; Fazio, Simone; Monti, Andrea
Abstract Economic and policy incentives for biofuel development differ in the USA and the EU, but indicators of environmental sustainability that have emerged from recent scientific literature transcend political boundaries. We classified these indicators according to six dimensions of environmental sustainability that have been previously identified, providing a description of each, and relating them to proposed international standards for advanced biofuels. Advanced biofuel development can be a step toward environmentally sustainable energy if optimal standards for feedstock selection, management, production, and fuel conversion are explicitly targeted. Tools for assessing environmental sustainability exist, but have not yet been put to task in a standardized way for advanced biofuels. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd